Price transmission among different Atlantic salmon products in the U.S. import market. Issue 3 (2nd July 2016) - Singh, Kehar
ABSTRACT: The cross-commodity price transmission is an approach to derive meaningful results from the price information, and is mostly influenced by the substitutability and complementary relations among products. Using time series data collected from the National Marine Fisheries Statistics, the present study specified and estimated cross-commodity price transmission models for 13 salmon products imported in the U.S. market. The salmon products are differentiated by form, cut, source/origin, and production environment. The estimated cross-product price transmission elasticity and degree of substitutability among them varied considerably. Whole fresh farmed Canadian and Norwegian Atlantic salmon did not have any close import substitutes in the U.S. market among the salmon products considered in the study. A reduced pricing strategy would result in an increase in U.S. salmon import market share of Chilean and U.K. Atlantic fillet fresh, if the U.S. import demand for it is relatively own-price elastic.